Negoisasi Sebagai Upaya Alternative Penyelesaian Kredit Macet di Bidang Perbankan Secara Win-Win Solution - Dede Suana Ependi; Devi Siti Hamzah Marpaung (Wajah Hukum, 2021)
Banking is one of the sources of funds, including in the form of credit for the community. Banks in providing credit will be very careful and will go through a more in-depth analysis. However, in providing credit, often the credit given to the debtor cannot be returned on time. This condition is called bad credit. The purpose of this study is to determine what factors cause bad credit in the banking sector and how to solve it in non-litigation ways. The method used in this research is the juridical-normative method, in which the research is carried out by means of literature study of law books, statutory regulations, literature and other references. The results of this study indicate that the factors causing the occurrence of bad credit in the banking sector include failure to accept the debtor's business, bad faith from the debtor, the discovery of credit loans without the knowledge of the family which can lead to a lack of responsibility, credit abuse by debtors and the presence of debtors. debtors who work as laborers, farmers, fishermen so that their finances cannot be guaranteed at all times, but only at certain times. As for the way to settle bad credit through non-litigation channels, namely by negotiation which can be done in three ways including rescheduling, reconditioning, and restructuring.